Production, Characterization and Testing of Teak Leaf (Tectona grandis) Dye Extract on Cotton Fabric - Joshua, Y; Magomya, A. M; Gani, J; Asose, A.; Emmanuel, M (African Journal of Biochemistry and Molecular Biology Research, 2024)
The natural dye was extracted from the leaves of Tectona grand is using a Soxhlet extractor, and a percentage yield of 16.84% was obtained. The color of the dye extract is maroon. The dye extract was characterized using FTIR, GC-MS, AFM, and UV-visible spectroscopy. The results of AFM showed that the dye extract from teak leaf has a root mean square roughness of 2568.2 nm in the 50μm×50μm scan area, and FTIR characterization suggested the presence of N-H (amine), O-H (alcohol), C-H (alkane), C-H (alkane), C≡C (alkyne), C = C (alkene), C = O (carbonyl groups), alkyl ketone, alkyl amine, and alkyl halide functional groups in the dye extract. The GC-MS separated and identified 36 compounds. Among the compounds identified in the dye extract, cis-vaccenic acid has the highest percentage area (18.68%), and azobenzene has the lowest percentage area (0.37%). The chromophores in the dye extract are C≡N and N=N. The natural dye extract was applied to the cotton fabrics without mordant. The color fastness to washing shows 3-4 and 3 for color change and staining, respectively, while the color fastness to rubbing shows 3 and 2 for dry and wet rubbing respectively. The outcome of color fastness shows that the dye has poor affinity to remain on the fabric. Therefore, the use of different kinds of mordant is recommended.